Smart technologies, systems and applications first International Conference, SmartTech-IC 2019, Quito, Ecuador, December 2-4, 2019, Proceedings /: first International Conference, SmartTech-IC 2019, Quito, Ecuador, December 2-4, 2019, Proceedings. (2020) - Unknown
No abstract available